2001
DOI: 10.1093/pcp/pce031
|View full text |Cite
|
Sign up to set email alerts
|

The Chloroplast clpP Gene, Encoding a Proteolytic Subunit of ATP-Dependent Protease, is Indispensable for Chloroplast Development in Tobacco

Abstract: ClpP is a proteolytic subunit of the ATP-dependent Clp protease, which is found in chloroplasts in higher plants. Proteolytic subunits are encoded both by the chloroplast gene, clpP, and a nuclear multi gene family. We insertionally disrupted clpP by chloroplast transformation in tobacco. However, complete segregation was impossible, indicating that the chloroplast-encoded clpP gene has an indispensable function for cell survival. In the heteroplasmic clpP disruptant, the leaf surface was rough by clumping, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(127 citation statements)
references
References 38 publications
3
120
1
Order By: Relevance
“…Interestingly, all of these mutants have lesions in the chloroplast DNA-encoded ClpP (proteolytic) subunit of the Clp protease. Analyses of these mutants have revealed that ClpP is necessary for proper chloroplast biogenesis and shoot development (34)(35)(36) and for growth and the proteolytic disposal of cytochrome b 6 ͞f in the thylakoid membranes of Chlamydomonas (37,38). Further support for the necessity of ClpP is found in the observation that ClpP is retained and expressed in the degenerated plastid genome of Epifagus (39).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all of these mutants have lesions in the chloroplast DNA-encoded ClpP (proteolytic) subunit of the Clp protease. Analyses of these mutants have revealed that ClpP is necessary for proper chloroplast biogenesis and shoot development (34)(35)(36) and for growth and the proteolytic disposal of cytochrome b 6 ͞f in the thylakoid membranes of Chlamydomonas (37,38). Further support for the necessity of ClpP is found in the observation that ClpP is retained and expressed in the degenerated plastid genome of Epifagus (39).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chloroplast-encoded ClpP1 was shown to be essential for shoot development in tobacco (Shikanai et al, 2001;Kuroda and Maliga, 2003). In addition, antisense lines for ClpP4 and for ClpP6 (Sjögren et al, 2006) were investigated that could germinate, develop on soil, and produce seeds; these plants still expressed ClpP4 or ClpP6, albeit at low levels.…”
Section: Functional and Structural Contributions Of Clppr Subunits Tomentioning
confidence: 99%
“…Overexpression of CLPR3, but not CLPR2 or CLPR4, in clpr1-1 led to full complementation, indicating that ClpR1 is partially redundant to ClpR3 (Kim et al, 2009). In addition, ClpP1, the only plastid-encoded Clp subunit, was shown to be essential for leaf development in tobacco (Nicotiana tabacum; Shikanai et al, 2001;Kuroda and Maliga, 2003). A mutant in CLPR2 with approximately 20% residual CLPR2 mRNA and ClpR2 protein (clpr2-1; Rudella et al, 2006) and antisense lines against CLPP4 and CLPP6 ( Sjögren et al, 2006;Zheng et al, 2006) in Arabidopsis exhibited delayed chloroplast and plant development and a virescent or variegated phenotype.…”
mentioning
confidence: 99%
“…By contrast, the plastid ClpP protease appears to have an essential role based on the experimental failure to generate homoplasmic knockout lines of clpP1 in the three photosynthetic organisms: Nicotiana tabacum (Shikanai et al, 2001;Kuroda and Maliga, 2003), Synechococcus elongatus pcc 7942 (Schelin et al, 2002;Barker-Aström et al, 2005), and C. reinhardtii (Huang et al, 1994). In this alga, attenuated expression of ClpP1 was achieved by replacing the AUG start codon of ClpP1 with AUU, a less efficient initiation codon (Majeran et al, 2000).…”
Section: Introductionmentioning
confidence: 99%